Identifying the Specific Root Microbiome of the Hyperaccumulator Noccaea brachypetala Growing in Non-metalliferous Soils - Martos, Soledad; Busoms, Sílvia; Pérez-Martín, Laura; Llugany, Mercè; Cabot, Catalina; Poschenrieder, Charlotte (Frontiers in Microbiology, 2021)
Noccaea brachypetala is a close relative of N. caerulescens, a model plant species used in metal hyperaccumulation studies. In a previous survey in the Catalan Pyrenees, we found two occidental and two oriental N. brachypetala populations growing on non-metalliferous soils, with accumulated high concentrations of Cd and Zn. Our hypothesis was that the microbiome companion of the plant roots may influence the ability of these plants to absorb metals. We performed high-throughput sequencing of the bacterial and fungal communities in the rhizosphere soil and rhizoplane fractions. The rhizobiomes and shoot ionomes of N. brachypetala plants were analysed along with those from other non-hyperaccumulator Brassicaceae species found at the same sampling locations. The analyses revealed that microbiome richness and relative abundance tended to increase in N. brachypetala plants compared to non-hyperaccumulator species, regardless of plant location. We confirmed that the root compartment is a key factor in describing the community composition linked to the co-habiting Brassicaceae species, and the rhizoplane fraction contained the specific and rare taxa associated with each species. N. brachypetala plants harboured a similar relative abundance of fungi compared to the other plant hosts, but there was a notable reduction in some specific taxa. Additionally, we observed an enrichment in the hyperaccumulator rhizoplane of previously described metal-tolerant bacteria and bacteria involved in nitrogen cycling. The bacteria involved in the nitrogen cycle could contribute indirectly to the hyperaccumulator phenotype by improving soil quality and fertility. Our results indicate that N. brachypetala captures a particular prokaryotic community from the soil. This particular prokaryotic community may benefit the extraction of metal ions and/or improve plant nutrition. Our research identified satellite groups associated with the root niche of a hyperaccumulator plant that may assist in improving biological strategies in heavy metal remediation.